Genetic divergence in germplasm collections of turmeric (Curcuma longa L.) - Reddy, M Ganesh, A Manohar Rao, P Venkat Rao, Y (Journal of Spices and Aromatic Crops, 2005)
Fifty four turmeric (Curcuma longa) cultivars were evaluated at Jagtial (Andhra Pradesh) by subjecting to D2 statistic to assess the genetic diversity available in the cultivars. The D2 analysis showed wide diversity among the cultivars and they were grouped into six clusters. Inter-cluster distance values also showed wide genetic divergence among the cultivars. Based on cluster-mean values, the cultivars PTS-38 and Duggirala in cluster I (high cured yield), PCT-5 and PCT-8 in cluster III (high curcumin, essential oil and oleoresin contents) and PCT-13, PCT-14 and PCT-10 in cluster IV (short duration, medium yield with good curcumin content) were identified as potential parents for future breeding programmes.